Reliability Allocation Method of NC Servo Tool Rest Based on Improved Comprehensive Factor Method - CHEN Chuanhai; GUO Jinyan; LIU Mingying; LIU Zhifeng; YANG Zhaojun; QI Baobao (Journal of Harbin University of Science and Technology, 2023)
Aiming at the uncertainty caused by independent consideration of influencing factors and expert scoring in the process of reliability allocation, a reliability allocation method of NC tool holder based on grey correlation theory, fuzzy set theory and ordered weighted averaging operator is proposed The technical level,importance, complexity, operation environment, maintainability, cost effectiveness ratio and other influencing factors are comprehensively considered.The factors are refined and organized into layers to establish a layered comprehensive factor evaluation model. Additionally, evaluation criteria are provided. Based on the statistical data obtained from the field test, the global index model of the subsystem is established to obtain the global index of each subsystem Taking the failure rate as the allocation index, the overall failure rate of the NC tool holder system is allocated to each subsystem to complete the reliability allocation of the NC servo tool holder.The obtained reliability allocation result is 2.193×10-5 for the rest drive system, 1.645×10-5 for the transmission device, 2.547×10-5 for the locking, loosening and positioning device, 1.345×10-5 for the cutter head signal device, 4.589×10-5 for the sealing and fastening device, and 4.544×10 -5 for the connecting line and interface, which is consistent with the actual engineering condition of NC servo tool rest.